PROBLEMATIKA PENERAPAN SOAL BERBASIS NUMERASI PADA PEMBELAJARAN MATEMATIKA KELAS V SEKOLAH DASAR DI KABUPATEN LOMBOK BARAT - Ruhil Ismafitri; Makbul Muksar; Syamsul Hadi; Herjan Haryadi (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2024)
Numeracy skills are needed in all aspects of life. Numeracy is the ability to apply number concepts and mathematical skills in everyday life as well as being able to use mathematics practically and have an understanding of information that is expressed mathematically.This study uses a qualitative approach with a multi-case study design. Data were collected through observation, interviews and documentation. The data analysis process is done through single case data analysis and cross case data analysis. The location of the study was conducted at three elementary schools in West Lombok regency, namely SDN 3 Kuripan, SDN 2 Jembatan Kembar Timur and SDN 4 Dasan Geres. The findings from the three schools showed that teachers in constructing numeracy-based problems refer to the components of the numeracy AKM but still in the form of simple questions. In pemanfataanya, numeracy-based questions are not done routinely and according to the needs of ANBK only. The lack of workshops and references as well as the distribution of teaching materials on numeracy in schools is a significant obstacle to the use of numeracy-based problems. While the supporting factor in the form of online sites that discuss examples of numeracy problems and the form of contextualization of the problem in the form of personal, socio-cultural and scientific contexts are still minimal.